Aberrant status and clinicopathologic characteristic associations of 11 target genes in 1,321 Chinese patients with lung adenocarcinoma - Zhao, Mengnan; Zhan, Cheng; Li, Ming; Yang, Xiaodong; Yang, Xinyu; Zhang, Yong; Lin, Miao; Xia, Yifeng; Feng, Mingxiang; Wang, Qun (Journal of Thoracic Disease; Vol 10, No 1 (January 31, 2018): Journal of Thoracic Disease, 2018)
Background: The aberrant status of target genes and their associations with clinicopathologic characteristics are still unclear in primary lung adenocarcinoma. Methods: The common mutations and translocations of nine target genes were evaluated in 1,247 specimens of surgically-resected primary lung adenocarcinoma. Immunohistochemistry was used to analyze the expressions of programmed death-1 (PD-1)/programmed death-ligand 1 (PD-L1) in 731 specimens. The frequency of the aberrations and their associations with clinicopathologic characteristics were analyzed. Results: Overall, 952 (76.3%) of 1,247 patients harbored at least one target mutation or translocation: epidermal growth factor receptor (EGFR) (729, 58.5%), v-Ki-ras2 Kirsten rat sarcoma viral oncogene homolog (KRAS) (83, 6.7%), human epidermal growth factor receptor 2 (HER2) (82, 6.6%), anaplastic lymphoma kinase (ALK) (23, 1.8%), phosphoinositide-3-kinase catalytic alpha polypeptide (PIK3CA) (20, 1.6%), Ret proto-oncogene RET (15, 1.2%), ROS proto-oncogene 1 receptor tyrosine kinase (ROS1) (12, 1.0%), B-raf proto-oncogene (BRAF) (9, 0.7%), neuroblastoma RAS viral (v-ras) oncogene homolog (NRAS) (3, 0.2%). Fourteen (1.9%) of 731 patients were PD-1 positive and 95 (13.0%) were PD-L1 positive in tumor cells. In men and smokers, there were more frequent KRAS mutations (both P